Lung-targeted nano composite material as well as preparation method and application thereof
Nanocomposite materials prepared by using AIE photosensitizer loaded with carbon nitride two-dimensional nanosheet carriers have been solved, and the problem of difficulty in synchronizing diagnosis and treatment of existing lung targeted drugs has been achieved, efficient diagnosis and treatment of lung cancer, and excellent drug retention and local effect.
Patent Information
- Application Number
- CN202411349200.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing lung targeted drugs are difficult to achieve diagnosis and treatment synchronously, and the traditional imaging methods have low resolution, making it impossible to accurately identify early lung cancer tissues, resulting in delays in the disease.
A nanocomposite material including a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on its surface is used to load the AIE photosensitizer on the carbon nitride two-dimensional nanosheet through electrostatic force to form a nanocomposite material. The material is prepared by a stirring reaction and can be administered through tracheal spray.
Nanocomposites have excellent aggregation-induced luminescence properties and reactive oxygen generation ability, which can synchronize the diagnosis and treatment of lung cancer, enhance drug retention in the lungs, reduce the number of doses, and have the advantages of rapid onset of effects, high local drug concentration and few systemic adverse reactions.
Smart Images

Figure CN119587693A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biotechnology, and in particular to a lung-targeted nanocomposite material and a preparation method and application thereof. Background Art
[0002] The metastatic, diffusive and lethal nature of lung cancer endows lung cancer research with great significance. However, traditional treatment methods, such as chemotherapy and radiotherapy, are difficult to specifically enrich drugs in the lungs and have large side effects, resulting in poor treatment effects; traditional imaging methods, such as CT and MRI, have low resolution and poor accuracy, especially the inability to accurately identify subtle early cancerous tissues, leading to delayed treatment; moreover, traditional diagnosis and treatment methods cannot be achieved simultaneously, which also greatly limits the diagnosis and treatment efficiency of lung cancer.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lung-targeted nanocomposite material and a preparation method and application thereof, aiming to solve the problem that existing lung-targeted drugs cannot achieve diagnosis and treatment simultaneously.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect of the present invention, a lung-targeted nanocomposite material is provided, comprising a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on the surface of the carbon nitride two-dimensional nanosheet.
[0007] Optionally, the mass ratio of the carbon nitride two-dimensional nanosheets to the AIE photosensitizer is 1-10:1.
[0008] Optionally, the planar size of the carbon nitride two-dimensional nanosheet is 0.5-2 μm.
[0009] Optionally, the structure of the AIE photosensitizer is selected from
[0010] One of them.
[0011] Optionally, the carbon nitride two-dimensional nanosheet is proton-functionalized graphite phase carbon nitride.
[0012] Optionally, the AIE photosensitizer is loaded on the surface of the carbon nitride two-dimensional nanosheets through electrostatic force.
[0013] The second aspect of the present invention provides a method for preparing the nanocomposite material as described in the first aspect, comprising:
[0014] The carbon nitride two-dimensional nanosheets and the AIE photosensitizer are dissolved in a mixed solution of an organic phase and an aqueous phase, and stirred for reaction to obtain the nanocomposite material.
[0015] Optionally, the stirring reaction is carried out at a temperature of 10-35°C and for a time of 12-24 hours.
[0016] Optionally, after the stirring reaction, the process further includes washing with water and filtering.
[0017] The third aspect of the present invention provides a use of the nanocomposite material as described in the first aspect in preparing a drug for treating and diagnosing lung cancer.
[0018] Beneficial effects: The present invention provides a lung-targeted nanocomposite material, a preparation method thereof, and an application thereof, wherein the nanocomposite material comprises a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on the surface of the carbon nitride two-dimensional nanosheet. The nanocomposite material of the present invention has excellent aggregation-induced luminescence properties and reactive oxygen generation capabilities, which can not only play the diagnostic role of the photosensitizer, but also produce a good tumor elimination effect, and can simultaneously realize the diagnosis and treatment of lung cancer. In addition, the nanocomposite material has a suitable size, which can enhance the retention of drugs in the lungs, prolong the treatment time, and reduce the number of dosing times; it can also be administered through tracheal spray, and has the advantages of rapid onset of action, high local drug concentration, small dosage, convenient use, few systemic adverse reactions, and easy monitoring and dosage adjustment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 g-C3N4 in Example 1 of the present invention + Scanning electron microscopy image of the nanosheets.
[0020] Figure 2 This is a graph showing the fluorescence intensity changes of C3N4@TDP in different proportions in Example 1 of the present invention.
[0021] Figure 3 This is a graph showing the test results of the active oxygen generation capacity of C3N4, TDP and C3N4@TDP in Example 1 of the present invention.
[0022] Figure 4 This is a graph showing the gas production capacity test results of C3N4, TDP and C3N4@TDP in Example 1 of the present invention.
[0023] Figure 5 This is a graph showing the cellular dark toxicity and phototoxicity test results of C3N4, TDP and C3N4@TDP in Example 2 of the present invention.
[0024] Figure 6 This is a graph showing the results of the lung retention experiment of TDP and C3N4@TDP in Example 3 of the present invention.
[0025] Figure 7 This is a graph showing the experimental results of treating lung cancer in mice using C3N4@TDP in Example 4 of the present invention. DETAILED DESCRIPTION
[0026] The present invention provides a lung-targeted nanocomposite material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0027] Photosensitizers with the property of "aggregation-induced emission" (AIE) are an emerging and important material that is expected to achieve integrated cancer diagnosis and treatment. In 2001, Academician Tang Benzhong, a professor at the Hong Kong University of Science and Technology, proposed the concept of "aggregation-induced emission" and developed a series of compounds with aggregation-induced emission properties. When they are well dispersed, the rotors produce active rotation or the flexible parts vibrate after being excited, resulting in non-radiative inactivation of excited state molecules; when aggregated, the constraints caused by the close arrangement of molecules greatly restrict the intramolecular movement, hindering the non-radiative decay path, so they can emit fluorescence in the aggregated state. Compared with traditional aggregation-induced quenching (ACQ) materials, aggregation-induced emission materials have high luminescence efficiency and good photostability, and have great application potential in the visual tracking of metastatic lung cancer. At the same time, some AIE photosensitizers with specific structures also have phototherapy effects. They produce cytotoxic reactive oxygen species (ROS) (photodynamic therapy, PDT) or heat (photothermal therapy, PTT) under the stimulation of excitation light to kill tumors, and have the advantages of non-invasiveness, spatiotemporal selectivity, tumor specificity and high efficiency. The lung is a translucent organ with abundant alveolar tissue, which is very conducive to light penetration and internal scattering. AIE photosensitizers can effectively mark and efficiently kill tumor tissues, achieving the diagnosis and treatment effect of "pointing where to hit", providing a promising new solution for the integrated diagnosis and treatment of lung cancer.
[0028] Two-dimensional nanosheets, with their anisotropy, rich surface properties and unique functionality, have become the best candidate materials for lung-targeted carriers of AIE photosensitizers. First, two-dimensional nanosheets have great potential in lung targeting; second, their two-dimensional size and interlayer distance can be controlled by a simple ultrasonic exfoliation method, so that they have a large specific surface area, and the surface has rich functional groups and active sites, which can further effectively increase the drug loading through π-π interaction or hydrophilic-hydrophobic interaction, so that they have excellent performance in drug accumulation and other aspects; finally, two-dimensional nanosheets are not only carrier materials, but also have many functionalities, such as photothermal, photocatalytic and conductive properties, and have special performance in drug controlled release, radiotherapy, immunotherapy and other directions. The combination of two-dimensional nanosheets and AIE photosensitizers has also been reported. For example, Tang Benzhong's team found that the surface of monolayer or few-layer transition metal sulfides has an aggregation effect on AIE molecules, and AIE aggregates (DDTA) interact with monolayer MoS2 nanosheets to produce fluorescence enhancement or quenching phenomena; in addition, the interlayer gaps of multilayer α-ZrP nanosheets have a confining effect on the embedded AIE photosensitizers, and the fluorescence intensity of the system can be effectively enhanced by matching the α-ZrP interlayer spacing and the AIE molecule size; this team also found that PEG-modified AIE photosensitizers (PEG-TTPy) composite black phosphorus through electrostatic forces to make the system have good biocompatibility and even mitochondrial targeting. The composite material takes into account the fluorescence imaging effect, reactive oxygen generation ability and photothermal therapy effect of black phosphorus of PEG-TTPy, and has the effect of eliminating tumors.
[0029] It can be seen that AIE photosensitizers and two-dimensional nanosheets are the "best partners", but there are currently no reports in the field of integrated lung targeted diagnosis and treatment.
[0030] Based on this, an embodiment of the present invention provides a lung-targeted nanocomposite material, comprising a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on the surface of the carbon nitride two-dimensional nanosheet.
[0031] In one embodiment, the mass ratio of the carbon nitride two-dimensional nanosheets and the AIE photosensitizer is 1-10:1; for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.; in a preferred embodiment, the mass ratio of the carbon nitride two-dimensional nanosheets and the AIE photosensitizer is 5:1.
[0032] In one embodiment, the planar size of the carbon nitride two-dimensional nanosheet is 0.5-2 μm; for example, it can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2.0 μm, etc.; in a preferred embodiment, the planar size of the carbon nitride two-dimensional nanosheet is 1.0 μm.
[0033] In one embodiment, the structure of the AIE photosensitizer is selected from
[0034] In one of the above, but not limited thereto, it can also be replaced by other types of AIE photosensitizers; in a preferred embodiment, the structure of the AIE photosensitizer is
[0035]
[0036] In one embodiment, the carbon nitride two-dimensional nanosheet is proton-functionalized graphite-phase carbon nitride.
[0037] In one embodiment, when the carbon nitride two-dimensional nanosheet is a proton-functionalized graphite-phase carbon nitride, the AIE photosensitizer is loaded on the surface of the carbon nitride two-dimensional nanosheet through electrostatic force.
[0038] The present invention also provides a method for preparing the nanocomposite material as described above, comprising:
[0039] The carbon nitride two-dimensional nanosheets and the AIE photosensitizer are dissolved in a mixed solution of an organic phase and an aqueous phase, and stirred for reaction to obtain the nanocomposite material.
[0040] In one embodiment, the stirring reaction temperature is 10-35°C; for example, it can be 10°C, 12°C, 15°C, 18°C, 20°C, 22°C, 25°C, 27°C, 30°C, 32°C, 35°C, etc.
[0041] In one embodiment, the stirring reaction time is 12-24 hours; for example, it can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, etc.
[0042] In one embodiment, after the stirring reaction, water washing and filtering are further included.
[0043] In one embodiment, the organic phase is selected from one or more of methanol, ethanol, tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO), but is not limited thereto; in a preferred embodiment, the organic phase is DMSO.
[0044] In one embodiment, in the mixed solution of the organic phase and the aqueous phase, the ratio of the organic phase to the aqueous phase is 1:9-9:1; for example, it can be 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1, etc.; in a preferred embodiment, the ratio of the organic phase to the aqueous phase is 5:5.
[0045] In one embodiment, the carbon nitride two-dimensional nanosheets and the AIE photosensitizer are dissolved in a mixed solution of an organic phase and an aqueous phase, and the concentration of the carbon nitride two-dimensional nanosheets in the mixed solution is 10-100 μg / mL; for example, it can be 10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL, 60 μg / mL, 70 μg / mL, 80 μg / mL, 90 μg / mL, 100 μg / mL.
[0046] In one embodiment, the carbon nitride two-dimensional nanosheets and the AIE photosensitizer are dissolved in a mixed solution of an organic phase and an aqueous phase, and the concentration of the AIE photosensitizer in the mixed solution is 1-10 μg / mL; for example, it can be 1 μg / mL, 2 μg / mL, 3 μg / mL, 4 μg / mL, 5 μg / mL, 6 μg / mL, 7 μg / mL, 8 μg / mL, 9 μg / mL, 10 μg / mL.
[0047] In a specific technical solution of the present invention, the following steps are included:
[0048] In an inert atmosphere, graphite phase carbon nitride (g-C3N4) was prepared by calcining dicyandiamide at 550°C with a heating rate of 2.3°C / min, and then kept at 550°C for 4-5 hours to obtain bulk g-C3N4 material. At room temperature, 1-2g of bulk g-C3N4 was protonated in 20-50mL of 8-10M HCl by vigorously stirring the solution for 1-2 hours, filtered, and repeatedly washed with water to remove ultra-concentrated HCl. Then 20-50mg of protonated g-C3N4 was dispersed in 100-200mL of deionized water and ultrasonically treated for 1-3 hours. The mixture after ultrasonication was centrifuged at 3000rpm to remove unflaked aggregates, leaving a uniform aqueous dispersion of proton-functionalized g-C3N4 nanosheets;
[0049] The above-mentioned proton-functionalized g-C3N4 nanosheet aqueous solution was subjected to continuous ultrasonication for 1-3 h to obtain g-C3N4 nanosheets with a size of about 0.5-2 μm. + Nanosheets;
[0050] Take 1-20mL g-C3N4 + The nanosheet aqueous solution (10-100 μg / mL) and 1-20 mL of TDP aqueous solution (1-10 μg / mL) were added to 1-50 mL of DMSO, stirred at room temperature for 12-24 h, repeatedly washed with water, and filtered to obtain a nanocomposite material.
[0051] An embodiment of the present invention provides a use of the nanocomposite material as described above in preparing a drug for treating and diagnosing lung cancer.
[0052] The present invention will be further described below by means of specific examples.
[0053] Example 1
[0054] This embodiment provides a lung-targeted nanocomposite material, and performs spectral property tests, photo-induced reactive oxygen generation capacity evaluation, and gas production capacity evaluation on the nanocomposite material. The details are as follows:
[0055] (1) Preparation of nanocomposites
[0056] ① Preparation of AIE photosensitizer
[0057] The preparation method of AIE photosensitizer refers to patent CN 115490846 A. In this embodiment, the structural formula of the AIE photosensitizer (TDP) is as follows:
[0058]
[0059] ② Preparation of carbon nitride two-dimensional nanosheets
[0060] In an inert atmosphere, graphite phase carbon nitride (g-C3N4) was prepared by calcining dicyandiamide at 550°C with a heating rate of 2.3°C / min, and then kept at 550°C for 4 hours to obtain bulk g-C3N4 material. At room temperature, 1g of bulk g-C3N4 was protonated in 25mL of 10MHCl by vigorously stirring the solution for 1 hour, filtered, and repeatedly washed with water to remove ultra-concentrated HCl. Then 50mg of protonated g-C3N4 was dispersed in 100mL of deionized water and ultrasonically treated for 2 hours. The mixture after ultrasonication was centrifuged at 3000rpm to remove unflaked aggregates, leaving a uniform aqueous dispersion of proton-functionalized g-C3N4 nanosheets.
[0061] The above-mentioned proton-functionalized g-C3N4 nanosheet aqueous solution was subjected to continuous ultrasonication for about 2 h to obtain g-C3N4 nanosheets with a size of about 1 μm. + Nanosheets, such as Figure 1 shown.
[0062] ③ Preparation of nanocomposites
[0063] Take 10mL of g-C3N4 with different concentrations respectively + Nanosheet aqueous solutions (10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL) and 10 mL of TDP aqueous solution (10 μg / mL) were added to 20 mL of DMSO, stirred at room temperature for 24 h, and repeatedly washed with water and filtered to obtain C3N4@TDP in different proportions, i.e., nanocomposites.
[0064] (2) Spectral property test
[0065] The aggregation-induced emission properties of TDP (10 μM) in C3N4@TDP with different ratios were evaluated, and the fluorescence spectra were shown in Figure 2. Figure 2 As shown. Figure 2 It can be seen that in different proportions of C3N4@TDP, the aggregation-induced emission properties of TDP are linearly related to the proportion.
[0066] Subsequent experiments were carried out using C3N4@TDP with a ratio of C3N4:TDP = 5:1.
[0067] (3) Evaluation of Photoinduced Reactive Oxygen Generation Capacity
[0068] DCFH-DA was used as an indicator to evaluate the reactive oxygen production ability of C3N4, TDP and C3N4@TDP. 0.5 mL of DCFH-DA (0.001 M) ethanol solution was added to 2 mL of NaOH (0.01 M) solution for activation to obtain DCFH. 10 mL of PBS (PH 7.4) was added to adjust the pH of the solution and the solution was kept away from light. DCFH (5 μM) was used to evaluate the reactive oxygen production ability of C3N4, TDP and C3N4@TDP (0.2 μM) in PBS (PH 7.4) solution. They were irradiated with 660 nm laser respectively, and the fluorescence intensity at 525 nm at different time points under 488 nm excitation was recorded using a fluorescence spectrophotometer to obtain the fluorescence enhancement factor. The experimental results are as follows: Figure 3 As shown. Figure 3 It can be seen that C3N4@TDP has a strong ROS production ability under the irradiation of 660nm laser.
[0069] (3) Evaluation of gas production capacity
[0070] Gas chromatography was used to measure the ability of C3N4, TDP and C3N4@TDP to produce CO, CH4, H2 and O2. Figure 4 As shown. Figure 4 It can be seen that the gas production capacity of C3N4@TDP is significantly enhanced and further enhanced under CO2 supply conditions.
[0071] Example 2
[0072] This example provides an anti-proliferation experiment of C3N4@TDP (5:1) on breast cancer 4T1 cells by phototherapy in Example 1. The details are as follows:
[0073] The test cells in this example are breast cancer cells 4T1 cells; the test drugs are C3N4, TDP and C3N4@TDP; and the light source used is a 660nm laser.
[0074] The cells in the logarithmic growth phase were digested with trypsin and resuspended in complete medium to form a cell suspension.3 The cells were inoculated into 96-well plates at a density of 100 μM / well and cultured in a 37°C, 5% CO2 incubator. After 24 h, different concentrations of C3N4, TDP, and C3N4@TDP were added to make the final concentrations of 0.5, 1, 2, 3, 4, and 5 μM samples, respectively. The plates were cultured for 12 h and then illuminated (power 0.3 W / cm 2 660nm laser for 5 minutes). At the same time, the experimental group without light under the same experimental conditions also underwent dark toxicity study. After another 12 hours of culture, the cells were washed 3 times with PBS solution, and then cultured in the dark for 2 hours with fresh culture medium containing 10% CCK-8 without FBS. The absorbance value (OD value) at 450nm was tested with a microplate reader. The corresponding cell survival rate was calculated using the following formula: Cell survival rate (%) = (OD sample-OD background) / (OD control-OD background) × 100%. The experimental results are shown in Figure 5 As shown. Figure 5 It can be seen that when the drug concentration was 100 μg / mL, the cell survival rate of the control group that was not irradiated by laser exceeded 95%, proving that the compound had low dark toxicity and good biocompatibility. The cell survival rate of the C3N4@TDP group was almost zero after laser irradiation, proving that C3N4@TDP has a significant phototherapy anti-proliferation effect on breast cancer 4T1 cells.
[0075] Example 3
[0076] This example provides a retention experiment of C3N4@TDP (5:1) in the lungs in Example 1. The details are as follows:
[0077] TDP or C3N4@TDP in PBS (1 mg / mL, 25 μL) was injected into the lungs of mice with lung cancer by tracheal spray administration. The mice were dissected at different time points, and the residual molecules in the lungs of the mice were imaged by fluorescence imaging using a small animal imaging device. Figure 6 As shown. Figure 6 It can be seen that compared with TDP molecules, C3N4@TDP has better retention in lung cancer tissue, which is conducive to prolonging the window period of drug treatment and is gradually excreted through metabolism within 72 hours. The reason is that the diameter of the two-dimensional nanosheet is relatively large, which can hinder small molecules from passing through lung epithelial cells, thereby prolonging the metabolism time.
[0078] Example 3
[0079] This example provides an evaluation of the therapeutic effect of C3N4@TDP (5:1) on lung cancer in Example 1. The details are as follows:
[0080] The PBS solution of C3N4@TDP (1 mg / mL, 25 μL) was injected into the lungs of lung cancer mice by tracheal spray administration, and then the lungs of the mice were irradiated with laser (660 nm laser, 0.3 W / cm 2 , 5min), and then the lung cancer tissue was imaged by bioluminescence imaging using a small animal imager. It can be found that after treatment with C3N4@TDP, the lung cancer tissue of mice gradually disappeared and there was no recurrence within 15 days, proving that C3N4@TDP has a good tumor elimination effect.
[0081] In summary, the present invention provides a lung-targeted nanocomposite material, a preparation method thereof, and an application thereof, wherein the nanocomposite material comprises a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on the surface of the carbon nitride two-dimensional nanosheet. The nanocomposite material of the present invention has excellent aggregation-induced luminescence properties and reactive oxygen generation capabilities, which can not only play the diagnostic role of the photosensitizer, but also produce a good tumor elimination effect, and can simultaneously realize the diagnosis and treatment of lung cancer. In addition, the nanocomposite material has a suitable size, which can enhance the retention of drugs in the lungs, prolong the treatment time, and reduce the number of dosing times; it can also be administered by tracheal spray, and has the advantages of rapid onset, high local drug concentration, small dosage, convenient use, few systemic adverse reactions, and easy monitoring and dosage adjustment.
[0082] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A lung-targeted nanocomposite material, characterized in that: The invention comprises a carbon nitride two-dimensional nanosheet and an AIE photosensitizer loaded on the surface of the carbon nitride two-dimensional nanosheet.
2. The nanocomposite material according to claim 1, characterized in that The mass ratio of the carbon nitride two-dimensional nanosheets to the AIE photosensitizer is 1-10:
1.
3. The nanocomposite material according to claim 1, characterized in that The plane size of the carbon nitride two-dimensional nanosheet is 0.5-2 μm.
4. The nanocomposite material according to claim 1, characterized in that The structure of the AIE photosensitizer is selected from One of them.
5. The nanocomposite material according to claim 1, characterized in that The carbon nitride two-dimensional nanosheet is proton-functionalized graphite phase carbon nitride.
6. The nanocomposite material according to claim 5, characterized in that The AIE photosensitizer is loaded on the surface of the carbon nitride two-dimensional nanosheet through electrostatic force.
7. A method for preparing the nanocomposite material according to claims 1 to 6, characterized in that: include: The carbon nitride two-dimensional nanosheets and the AIE photosensitizer are dissolved in a mixed solution of an organic phase and an aqueous phase, and stirred for reaction to obtain the nanocomposite material.
8. The method for preparing the nanocomposite material according to claim 7, characterized in that: The stirring reaction is carried out at a temperature of 10-35°C and for a time of 12-24 hours.
9. The method for preparing the nanocomposite material according to claim 7, characterized in that: After the stirring reaction, the process further comprises washing with water and filtering.
10. Use of the nanocomposite material according to claims 1 to 6 in preparing drugs for treating and diagnosing lung cancer.
Citation Information
Patent Citations
C3N4 nanocomposite, preparation method and application of C3N4 nanocomposite
CN105535972A
Diagnosis and treatment integrated nanomaterial as well as preparation method and application thereof
CN111529720A
Water-soluble near-infrared two-region aggregation-induced emission material as well as preparation method and application thereof
CN115490846A
Method for synthesizing protonated carbon nitride nanosheet / conducting polymer composite material through low-temperature photopolymerization induction under atmosphere regulation and control
CN116970108A
Preparation method and application of hepatic fibrosis targeted AIE carbon nitride-based nanoparticles
CN117017944A